Home » Blog » Prove DeMoivre’s theorem using complex numbers

Prove DeMoivre’s theorem using complex numbers

  1. Prove DeMoivre’s theorem,

        \[ (\cos \theta + i \sin \theta)^n = \cos (n \theta) + i \sin (n \theta), \]

    for all \theta \in \mathbb{R} and all n \in \mathbb{Z}_{>0}.

  2. Prove the triple angle formulas for sine and cosine,

        \[ \sin (3 \theta) = 3 \cos^2 \theta \sin \theta - \sin^3 \theta, \qquad \cos (3 \theta) = \cos^3 \theta - 3 \cos \theta \sin^2 \theta, \]

    by letting n = 3 in part (a).


  1. Proof. Since \cos \theta + i \sin \theta = e^{i \theta} we have

        \[ (\cos \theta + i \sin \theta)^n = (e^{i \theta})^n = e^{ni \theta} = \cos (n \theta) + i \sin (n \theta). \qquad \blacksquare \]

  2. Letting n = 3, we first apply DeMoivre’s theorem to get

        \[ (\cos \theta + i \sin \theta)^3 = \cos (3 \theta) + i \sin (3 \theta). \]

    On the other hand, we can expand the product,

        \[  (\cos \theta + i \sin \theta)^3 = \cos^3 \theta + 3 i \cos^2 \theta \sin \theta - 3 \cos \theta \sin^2 \theta - i \sin^3 \theta \]

    Equating real and imaginary parts from the two expressions we obtain the requested identities:

        \[ \cos  (3 \theta) = \cos^3 \theta - 3 \cos \theta \sin^2 \theta \quad \text{and} \quad \sin (3 \theta) = 3 \cos^2 \theta \sin \theta - \sin^3 \theta.  \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):